Learner Support Services and Performance of the Students: A Survey on BBM (Online) Degree Programme of the University of Jaffna, Sri Lanka - Rathiranee, Y.; Nimalathasan, B. (JUICE- 2012 University of Jaffna, 2012)
A critical element of an effective succession program for online students is learner support services. The students’ performance depends on variety of factors and the learner support also is important to determine the performance. In the conventional method of teaching students can get all support from the institution. But in the Online teaching method there is no face to face interaction between students and teachers, students feel isolation and decrease in motivation level to study because of lack of self direction and management,. Therefore, the present study is designed to linkage between learner support services and students’ performance of the Bachelor of Business Management (BBM) Online Degree Programme in the University of Jaffna. The study suitably used both primary and secondary data. In this case, the researchers selected 60 students from BBM online degree programme conveniently. The opinions of thirty nine respondents were captured from questionnaire. Correlation and Regression analysis have been made. The results revealed that there is a significant relationship between the learner support services and performance of the students because the learner support services and the students’ performance have strong positive correlation at the 0.01 significant levels. Further it is concluded that the students’ performance depends on effective learner support services. To avoid the drawbacks of learner support services and the possible suggestions from the study by getting feedback from the students that the facilities such as usage of modern technology, ie using video conferencing, uploading the contents with PowerPoint presentation with sound recording and the advance instructions regarding examination and other face to face activities and the effective administrative procedures should be enhanced as learner support services in order to improve the performance. Outcomes of the study would benefit the academicians, researchers, policy makers, and practitioners of Sri Lanka and other similar countries.
Keywords: Learner Support Services; Online Learning; Students’ Performance